Aplikasi Pembelajaran Interaktif Berbasis Augmented Reality pada Mata Pelajaran Sistem Komputer di SMK YPKK 1 Sleman - Suci Dwi Ramadhani; Oktavia Hardiyantari (Journal of Research and Investigation in Education, 2025)
Interactive learning media is a teaching method that utilizes digital technology to convey information and facilitate active interaction between students and the subject matter. In this way, students can participate directly in learning in a more interesting and interactive way. The subject of computer systems is an important subject in the RPL department. However, in this subject, students often have difficulty receiving learning well due to the lack of practical tools available at school, which causes student completion scores to remain below 10%. This study aims to develop, test the feasibility, and effectiveness of interactive learning media based on augmented reality for the subject of computer systems in the RPL department at SMK YPKK 1 Sleman. The research method used is Research and Development (R&D) with the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The development was carried out using Unity 3D software with the help of the Vuforia SDK plugin. The results of the study are interactive learning media applications based on augmented reality for the subject of computer systems in class X of the RPL department. Alpha testing and beta testing showed results of 82% from media experts, 91.1% from material experts, and 86.94% from students, which is included in the Very Feasible category. The effectiveness test showed a score of 69%, which is included in the Quite Effective category. Based on this test, the learning media is very feasible and quite effective to be used as a learning medium, and can help the teaching and learning process.